Penerapan Algoritma Certainty Factor pada Sistem Pakar Diagnosis Penyakit Creutzfeldt-Jakob Disease - Alex Wenda; Saludin Saludin; Sitti Nur Alam; Edy Winarno; Devin Mahendika (Universitas Budi Darma, 2023)
Indonesia is a country that is active in the livestock sector, one of which is cattle farming. However, not many cows are affected by mad cow disease where this disease can be transmitted to humans by consuming the beef itself. This Gina cow disease, if it has been infected with humans, is called Creutzfeld-Jakob disease, where this disease can attack any part of the human body, namely the nervous tissue in the human brain so that it can destroy human brain cells and cause small holes in the brain automatically. gradually, the severity of this disease can claim a person's life if proper medical treatment is not carried out. This disease can cause death within one year after the symptoms are indicated as creutzfeld-jakob disease. To make it easier for an expert to diagnose a disease, a system can be used, namely an expert system with a certainty factor algorithm that determines the confidence value based on the percentage of the final Cfcombine value of the various types of symptoms that exist, so that the percentage value of the resulting confidence level is 89%.